Examining the Impact of E-Government on Corporate Social Responsibility Performance: The Mediating Effect of Mandatory Corporate Social Responsibility Policy, Corruption, and Information and Communication Technologies Development During the COVID era - Avotra, Andrianarivo Andriandafiarisoa Ralison Ny; Chengang, Ye; Sandra Marcelline, Tsimisaraka Raymondo; Asad, Ali; Yingfei, Yang (Frontiers in Psychology, 2021)
During the Covid-19 era, this research will explore and analyze the link between e-government and corporate social responsibility. In addition, mandatory corporate social responsibility, institutional quality, information and communication technology, and corruption as mediators will also been explored in this study. This research seeks to answer the issue of how e-government affects corporate social responsibility and how other mediating variables might influence this connection. Furthermore, this study developed a total of 13 hypotheses based on these questions, four of which have mediating effects. The theoretical underpinning for the proposed study paradigm is provided by stakeholder theory, which has been established based on prior literature. The general philosophy is positivism, and the research has deductive nature. The information was gathered from 305 managers across four industries: information technology, online services, online education, and logistics and supply chain. Data was collected using a random convenience sampling approach. The Partial Least Square Sequential Equation Modeling (PLS-SEM) research analysis approach was applied in tis study for the analysis. The measurement step demonstrated that all constructs and indicators are valid and trustworthy enough to be utilized in the future. The results of the structural model evaluation revealed that e-government had a negative influence on corporate social responsibility, with three of the four mediating roles proving to be completely mediated. As a result, the government and relevant stakeholders should take these results into account when formulating e-government policies.